An unbreakable world - Hutchings, Ren (Solaris, 2025)
"If something seems too good to be real, you've got to get out of there. That's the rule that Page Found has always followed. She's a petty thief with no memory of her past, scrounging to survive on a backwater outpost--until she's kidnapped by one of her marks. Her kidnappers--the cruel, self-serving Zhak and the tough maverick Maelle--plan to pass Page off as a monk from an ancient, isolated planet to help them capture a treasure-filled ship. If Page is willing to play along, they all stand to become richer than they can imagine. Everyone is keeping secrets, and Maelle finds her loyalties conflicted as she gets closer to their captive. Page can't remember the last time she counted on anyone. But to navigate this deception, she and Maelle will have to trust each other to survive."--Publisher description.